Rambutan Commodity Development Strategy as Regional Potential Product - Pujiati, Amin; Nihayah, Dyah Maya; Setiyani, Rediana (Semarang State University, 2016)
The potential product of a region needs to be developed in order to improve the social welfare. Commonly, at harvest time, there is abundant horticulture commodity. Unluckily, the price of the commodity drops significantly. In other words, it costsÂ extremely cheap. The purpose of research is analyzing the internal and external factors and determining an appropriate strategy for developing rambutan in Central Java, especially at Gunungpati District, Semarang, Central Java Province. The primary data of this research is obtained from 58 rambutan farmers that have been interviewed and have filled out the questionnaire forms. The secondary data is taken from the Central Bureau of Statistics, the monograph of the village and the internet by implementing the literature study method. Then, SWOT analysis is implemented for analizing the data. The internal factors that become the strengths are fertilized land for rambutan to grow and the farmersâ hereditary experiences in cultivating rambutan. Further, the lack of absorbing power of knowledge and technologies and the low existence of rambutan business are the weaknesses. Next, the external factor that becomes opportunity is the continuous increasing market demand, while the threat is the young generations having no interest in rambutan business. Finally, the stability (hold and maintain) strategy should be implemented for developing rambutan business